Mixed-load machine utilization improvement and transfer batch size optimization using hybrid simulation approach - Asih, Hayati Mukti (2014)
Current technological development has increased the competitiveness in the manufacturing system, especially for the electronic industry. This research is based on case company in the automatic testing and label printing processes of a multinational hard disk drive (HDD) manufacturing system with the objective of improving the tester utilization while achieving the production target. The problem is complex as the testers are employed to simultaneously load multiple product families. Each product family has several models with different testing durations. In addition, apart from the high product mixes for each product family undergoes different process flow making the problem more complicated. The company has difficulty to achieve the targeted tester utilization of 96%, as the current utilization is 71.14%. As the problem is too complicated to be solved by an analytical method, a hybrid simulation approach was employed to solve the operation machine allocation and the transfer batch size problem. Firstly, the problem of mixed-load tester was formulated through a mathematical model. Then, a simulation model was designed and developed to evaluate the scenarios of the mixed-load tester configurations. After that, the multi criteria decision making techniques were employed to determine the best scenario. Finally, the transfer batch size was optimized to improve system WIP. The final proposed configuration successfully increased the tester utilization by 24.89% and reduced the number of testers by 37.77% for Tester A and by 27.27% for Tester B while improving the throughput by 6.88% compared to the current system. In addition, the transfer batch size was reduced from 120 units to 86 units and system WIP was successfully reduced by 6.43%.